2020
DOI: 10.1016/j.ejca.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 in paediatric early-phase cancer clinical trials in Europe: A report from the Innovative Therapies for Children with Cancer (ITCC) consortium

Abstract: Introduction Data regarding real-world impact on cancer clinical research during COVID-19 are scarce. We analysed the impact of the COVID-19 pandemic on the conduct of paediatric cancer phase I-II trials in Europe through the experience of the Innovative Therapies for Children with Cancer (ITCC). Methods A survey was sent to all ITCC-accredited Early-Phase Clinical Trial Hospitals including questions about impact on staff activities, recruitment, patient care, supply of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…This is in line with site initiation visits cancellation reported by the Innovative Therapies for Children with Cancer consortium. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with site initiation visits cancellation reported by the Innovative Therapies for Children with Cancer consortium. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Yet the impact on clinical research 1 , 2 is unclear, even more so that different medical specialties may have been impacted differently. Although there have been, for instance, reports in oncology 3 , 4 , 5 (including pediatric oncology 6 , 7 ) there have been none of such extent for the broad field of pediatrics, where recent work includes calls to mitigate the impact on ongoing and future trials. 8 , 9 This is perhaps because children are less directly impacted by the COVID-19 disease.…”
mentioning
confidence: 99%
“…In order to limit the negative impact on patients, the EMA (European Medicines Agency) and many scientific societies have issued recommendations and guidelines in order to support the conduct of clinical trials in this patient setting while continuing to ensure patient safety. Nevertheless, a negative impact has been reported on ongoing and starting studies, especially in recruitment and enrollment, with protocol deviations as patients miss hospital visits as well as delayed data reporting or monitoring activity [29] , [30] .…”
Section: Impact Of Covid-19 Pandemic On Pediatric Cancer Clinical Trimentioning
confidence: 99%
“…Participants may no longer be able to visit the hospital to receive treatment [4], resulting in protocol deviations. The regular monitoring and auditing of trials may also be affected [5], leading trials to be postponed or terminated; this in turn can delay marketing of drugs and even lead to the scrapping of development plans for new drugs. Several studies from several countries have reported obvious decreases in the numbers of participants newly enrolled in trials, and many oncology clinical trials were suspended in April 2020 in several countries [6][7][8].…”
Section: Introductionmentioning
confidence: 99%